Influence of crack tip plasticity on fatigue behaviour of laser stake-welded T-joints made of thin plates. (February 2018) - Gallo, P.; Guglielmo, M.; Romanoff, J.; Remes, H.
Highlights: The paper investigates the crack tip plasticity of the laser stake-welded T-joints. The thickness of the plates is varied. For high load levels the thin joints have a higher crack driving force. Explanation of the different fatigue curve slopes for different thicknesses is given. Thin joints number of cycles to failure is estimated from the thick joints fatigue curve. Abstract: The paper investigates the crack tip plasticity of laser stake-welded T-joints when the thickness is varied. For thin joints, mixed-mode condition is dominant, and the Minimum Plastic Zone Radius (MPZR) criterion is employed to estimate the crack initiation direction. Subsequently, the same first-order plastic zone size r y as defined by Irwin is kept equal for the selected load levels in the MPZR direction, and finite element (FE) analyses are carried out to investigate the stress gradient over r y comparing different thicknesses. The results allow us to explain why the fatigue slope m is different for thin and thick joints. Moreover, a new method is proposed that permits the number of cycles to failure of thin joints to be derived directly from the fatigue curve of thick joints, employing an effective J-integral. The results prove that the method is able to give an estimation of the number of cycles to failure for thin joints with acceptable error. Graphical abstract: